Impacts of rs7528684 (−169T/C) on FCRL3, FOXP3, and IL-35 gene expressions and IgG-RF correlation: insights into the pathogenesis of rheumatoid arthritis - Mohamed Muzammil, S.; Asha Devi, S. (Frontiers in Genetics, 2026)
BackgroundThe Fc receptor-like protein 3 (FCRL3) gene encodes a transmembrane receptor that is predominantly expressed on the surfaces of regulatory T cells (Tregs). The single-nucleotide polymorphism (SNP) rs7528684 (−169T/C) in the FCRL3 gene has been hypothesised to enhance its expression, which in turn causes dysfunction of Tregs and results in loss of self-tolerance as well as diminished production of anti-inflammatory cytokines. This process triggers rapid proliferation of the autoreactive T cells and other immune cells, exacerbating the progression of rheumatoid arthritis (RA) and other autoimmune diseases.MethodsIn the current study, we screened the FCRL3 SNP rs7528684 to assess its association with the risk of RA in the Indian population. The screening was performed using high-resolution melting analysis, and the findings were confirmed via Sanger sequencing. We further analysed the impacts of rs7528684 on FCRL3, forkhead box protein 3 (FOXP3), and interleukin-35 (IL-35) gene expressions using quantitative real-time polymerase chain reaction. The gene expression correlation between FCRL3 and FOXP3 mRNA expression was analysed using Spearman’s rank correlation coefficient (ρ) analysis. Concurrently, the inflammatory serological biomarkers immunoglobulin G rheumatoid factor (IgG-RF) and C-reactive protein were evaluated in the RA patients.ResultsThe FCRL3 SNP rs7528684 C/C genotype was significantly associated with increased risk of RA in the Indian ethnicity (p = 0.0005). Furthermore, the C allele frequency was significantly elevated within the RA group (58.6%). Similarly, RA patients carrying the C/C genotype also exhibited higher FCRL3 mRNA expression levels than the controls (p = 0.0072). Additionally, FOXP3 and IL-35 mRNA expressions were downregulated in RA patients carrying the C/C genotype. The FCRL3 mRNA expression demonstrated a significant negative correlation with FOXP3 mRNA expression (ρ = - 0.5526, p = 0.0094, R2 = 0.3052) in RA patients. The results also showed positive correlations between the C/C genotype and IgG-RF-positive RA cases.ConclusionOur findings validate that the C/C genotype of the FCRL3 SNP rs7528684 is strongly associated with RA in the Indian ethnicity. This genotype is characterised by positive IgG-RF and upregulated FCRL3 and downregulated FOXP3 and IL-35 as key anti-inflammatory cytokines. Concurrently, FCRL3 and FOXP3 mRNA expression levels are inversely correlated.